Assessment of Pseudomonas aeruginosa biofilm-forming capacities from drinking water in water vending machine - N., Elexson; H., Sabrina; L., Dalene; B., Eddy; F. R., Nurul; P., Nasra; B., Grace; L., Nick; Z. J., Amirah; D. Z., Nur; N. A. B, Dayang; S., Manju; et al. (Rynne Lyan Resources, 2022)
The establishment of P. aeruginosa with biofilm formation in water vending machines may cause serious health issues to the consumers and its emergence has led to the public’s concern. This study aimed to assess the quality of water vending machines and to evaluate the biological contaminant P. aeruginosa in biofilm capacities. The qualities of the drinking water from a total of fifteen (n = 15) water vending machines at Kota Samarahan were evaluated based on physical and chemical parameters including pH value, turbidity, total of carbon (TOC), total dissolved solid (TDS) and total suspended solid (TSS). The colonies Enterobacteriaceae has been morphology characterized through biochemical tests and P. aeruginosa bacteria was identify through the PCR method. The results of the physical and chemical parameters complies with the authority standard including turbidity values found in conformance with values were lower than 0.1 NTU. Morphological analysis with a total of 66.7% (n = 10) was detected with the presence of Enterobacteriaceae, and a total of 40% (n = 6) of the isolates were found to be P. aeruginosa. This study extended by assessing the potential strength of biofilm formation. The microtiter assay performed in a 96-well polystyrene microtiter plate showed that 83.33% (n = 5) of the bacterial isolates have moderate potential as biofilm producers, while only 16.67% (n = 1) isolates were non-adherent and showed no potential in producing biofilm. The highest OD isolates found occupying moderate biofilm strength was (mean = 0.217) and the lowest moderate biofilm strength was (mean = 0.136). In conclusion, the significance and impact of the study displayed the qualities of water vending machines complies with Food Act 1983, Regulation 360C and Malaysian Drinking Water Quality, Ministry of Health 1983. However, the presence of biological contaminants may raise consumer concerns. This study had successfully assessed the potential strength of P. aeruginosa biofilm collected from water vending machines. Further microbiological assessments should be perform continuously to predict and eliminate any future risks related to water vending machines.